Determinan penerapan good governance pada pemerintah daerah Kota Bima - Darmawan, Imam; Ovriyadin, Ovriyadin; Nurulrahmatiah, Nafisah; Humairah, Marsya; Fitriani, Reza (Nur Science Institute, 2024)
This research aims to determine the factors that influence the implementation of Good Governance in the Bima City regional government. This research uses a quantitative approach method by distributing questionnaires. The population in this research is all 34 SKPDs in Bima City. The sampling technique used is Judgment Sampling (selection of samples based on considerations) in determining the sample, a non-random type of sample selection where the information obtained is generally adjusted to the research objectives or problems. In this research, the samples taken were all elements of the leadership of each Bima City SKPD, with considerations directly related to policy formulation and regional financial management. So, the sample in this study was 102 respondents. The data analysis tool uses Smart PLS. This research provides information that the Application of Information Technology, Quality of Human Resources, and Internal Control Systems influence the Implementation of Good Governance in the Bima City government. Likewise, implementing good governance affects the quality of financial reports in the Bima City government.